Photodynamic effect of 5,10,15,20-tetrakis[4-(3-N,N-imethylaminopropoxy)phenyl]chlorin towards the human pathogen Candida albicans under different culture conditions - Cordero Gabrielli, Paula Verónica (2021)
Photocytotoxic activity sensitized by 5,10,15,20-tetrakis[4-(3-N,N-dimethylaminopropoxy)phenyl]chlorin (TAPC) was investigated in Candida albicans under different culture conditions. Planktonic cells incubated with 2.5 µM TAPC were eradicated after 5 min irradiation with white light.Studies in the presence of reactive oxygen species scavengers indicated the involvement of mainly a type II mechanism. Furthermore, cell growth of C. albicans was suppressed in the presence of 5 µM TAPC. A decrease in pseudohyphae survival of 5 log was found after 30 min irradiation. However, the photokilling of this virulence factor reached a 1.5 log reduction in human serum. The uptake of TAPC by pseudohyphae decreased in serum due to the interaction of TAPC with albumin. The binding constant of the TAPC-albumin complex was ~104 M−1, while the bimolecular quenching rate constant was ~1012 s−1 M−1, indicating that this process occurred through a static process. Thus, the photoinactivation of C. albicans was considerably decreased in the presence of albumin. A reduction of 2 log in cell survival was observed using 4.5% albumin and 30 min irradiation. The results allow optimizing the best conditions to inactivate C. albicans under different culture conditions.